New Neotropical species of Pantisarthrus Förster, 1871 (Hymenoptera: Ichneumonidae) - Camargo, Luiza Figueiredo; Shimbori, Eduardo Mitio; Penteado-Dias, Angélica Maria (Zootaxa, 2020)
The Pantisarthrus genus is recorded for the first time from the Neotropical region and P. communis sp. nov., P. flavocingulatus sp. nov. and P. paraitinga sp. nov. are described and illustrated. A key to described species is provided.